ANALISIS FLUKTUASI HARGA BERAS KUALITAS MEDIUM DAN PREMIUM DI PASAR TRADISIONAL KOTA KUPANG DAN MAUMERE - Serly F Nenoharan; Doppy Roy Nendissa; I Wayan Nampa (Undana Press, 2021)
This study aims to find out how the price fluctuations of medium and premium quality rice are and also to see how the movement patterns that occur every month in the Inpres Naikoten 1 Kupang market and the Alok Maumere market. The data used in this study are secondary data. The data collection method used in the form of secondary data obtained through related institutions such as the Central Statistics Agency, in the completeness of primary data it is also necessary to conduct a survey of the two markets. Analysis of the data used in this study used Coefficient of Variation (CV) analysis (First Goal), while to see the pattern of rice price movements used graphical analysis (Second Goal). The results of this study indicate the level of rice price fluctuations that occurred in the Naikoten 1 Kupang Inpres Market and Alok Maumere Market in the period January 2018 - December 2020, it can be concluded that the CV obtained for the price of medium and premium quality rice in the Naikoten 1 Inpres Market Kupang and Alok Maumere Market in the period January 2018 – December 2021 ranged from 2.45% - 0.23% (Medium 1, Naikoten Inpres Market 1 Kupang), 2.38% - 0.44% (Premium 1, Naikoten Inpres Market 1 Kupang), 4.25% - 0.00% (Medium 1, Pasar Alok Maumere), 4.69% - 0.13% (Premium 1, Pasar Alok Maumere), it can be said that the level of fluctuations in the price of medium and premium quality rice in the two markets in the period January 2018 – December 2020 is said to fluctuate low, either good or bad. in the Naikoten 1 Inpres Market in Kupang and the Alok Maumere Market. In the pattern of price movements for medium and premium quality rice in both markets, it shows that the price movements that occurred were not not too many price changes that can be said to decrease or increase drastically.